2022
DOI: 10.3390/biom12091193
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29a Family as a Key Regulator of Skeletal Muscle Dysplasia in a Porcine Model of Intrauterine Growth Retardation

Abstract: MicroRNAs (miRNAs) play an essential role in many biological processes. In this study, miRNAs in the skeletal muscle of normal and intrauterine growth retardation (IUGR) neonatal piglets were identified by sequencing, and canonical miRNAs were functionally validated in vitro. A total of 403 miRNAs were identified in neonatal piglet skeletal muscle, among them 30 and 46 miRNAs were upregulated and downregulated in IUGR pigs, respectively. Upregulated miRNAs were mainly enriched in propanoate metabolism, endocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…miR-1 and miR-206 were the two miRNAs with the highest expression levels, which accounted for more than 94%. These results are consistent with our previous reports [33]. Both miR-1 and miR-206 are members of the miR-1 family and share a common seed sequence.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…miR-1 and miR-206 were the two miRNAs with the highest expression levels, which accounted for more than 94%. These results are consistent with our previous reports [33]. Both miR-1 and miR-206 are members of the miR-1 family and share a common seed sequence.…”
Section: Discussionsupporting
confidence: 94%
“…Our published study showed that miR-29a was significantly upregulated in IUGR pig skeletal muscle. In C2C12 cells, overexpression of miR-29a can play a functional role in inhibiting myocyte proliferation by targeting the mRNA-level expression of IGF1 and CCND1 [33]. In adult muscle stem cells, miR-29a mediates fibroblast growth factor-2 (FGF-2) to promote myoblast proliferation, and inhibition of miR-29a expression showed the opposite effect [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further screening revealed that IGF1 is likely among tRF-Glu-TTC-047 target genes, with IGF1 at the core of IUGR porcine skeletal muscle regulatory network. IGF1 has also been reported to be involved in the regulation of skeletal muscle development and associated with the occurrence of IUGR ( Zhu et al, 2022 ). The binding relationship between the 3′ UTR of IGF1 and tRF-Glu-TTC-047 was further confirmed by a dual-luciferase reporter system.…”
Section: Discussionmentioning
confidence: 99%